Factors Associated with Smoking Cessation in Pregnancy - Moore, Elizabeth; Blatt, Kaitlin; Chen, Aimin; Van Hook, James; DeFranco, Emily A. (American Journal of Perinatology, 2016)
Objective The objective of this study was to quantify the influence of various patient characteristics on early smoking cessation to better identify target populations for focused counseling and interventions.Study Design This study was a population-based retrospective cohort study of 1,003,532 Ohio live births more than 7 years (2006–2012). Women who quit smoking in the first trimester were compared with those who smoked throughout pregnancy. Logistic regression estimated the strength of association between patient factors and smoking cessation.Results The factors most strongly associated with early smoking cessation were non-white race and Hispanic ethnicity, at least some college education, early prenatal care, marriage, and breastfeeding. Numerous factors commonly associated with adverse perinatal outcomes were found to have a negative association with smoking cessation: low educational attainment, limited or late prenatal care, prior preterm birth, age < 20 years, age ≥ 35 years, and indicators of low SES. In addition, the heaviest smokers (≥ 20 cigarette/day) were least likely to quit (adjusted relative risk [RR], 0.35; 95% confidence interval 0.34, 0.36).Conclusion Early prenatal care and initiation of breastfeeding before discharge from the hospital are associated with increased RR of quitting early in pregnancy by 52 and 99%, respectively. Public health initiatives and interventions should focus on the importance of early access to prenatal care and education regarding smoking cessation for these particularly vulnerable groups of women who are at inherently high risk of pregnancy complications.
Keywords: pregnancy; smoking cessation; factors